Collaborative Guidance and Counseling for Southeast Asian Students’ Mental Health: A Comparative Study in Indonesia, Thailand, and Malaysia - Ramdani, Ramdani; Sitinjak, Theresia; Afdal, Afdal; Bin Abdul Razak, Amirul Fahmie; Darunkan, Thammasin (International Journal of Research in Counseling and Education, 2025)
This study investigates collaborative guidance and counseling practices to enhance secondary students’ mental health in Indonesia, Thailand, and Malaysia, highlighting the role of local cultural values. Using a qualitative comparative multi-case study design, data were collected through in-depth interviews, observations, and document analysis involving 60 students, 20 counselors, and 8 principals. Cross-case thematic analysis identified three key factors for effective collaboration: integration of cultural and spiritual values, adaptive interprofessional synergy, and participatory school leadership. Cultural constructs such as gotong royong in Indonesia, Kreng Jai in Thailand, and Rukun Negara in Malaysia underpin collaborative practices and support students’ psychological well-being. The study proposes a Cultural-Contextual Collaborative Counseling Model, emphasizing cultural embeddedness as a mediator linking collaboration to mental health outcomes. Findings contribute to culturally responsive counseling theories and inform educational policies that promote cross-cultural guidance practices across the ASEAN region